Techno-economic optimization model for polygeneration hybrid energy storage systems using biogas and batteries. (1st March 2021) - Wegener, Moritz; Villarroel Schneider, J.; Malmquist, Anders; Isalgue, Antonio; Martin, Andrew; Martin, Viktoria
Abstract: Renewable energy polygeneration systems are a viable alternative to fossil-fuel based systems, but storage solutions may be necessary when aiming for high sustainability and autonomy. As each storage technology has different strengths and weaknesses, combinations of various storage solutions may lead to better techno-economic performance than singular approaches. To this purpose, an optimization model including a novel dispatch control strategy for a hybrid energy storage system (HESS) is proposed, which uses biogas for long-term and batteries for short-term storage. The model optimizes for minimum lifetime costs while exploiting the biomass resources with maximum efficiency and quantifying the additional solar and battery capacities needed. It is applied in a case study with an innovative biomass-based polygeneration system in a rural locality of Bolivia to serve electricity, potable water, and bio-slurry as fertilizer. The results indicate that even with maximized efficiency of the biomass resource conversion, large PV and battery capacities are necessary to satisfy the electricity demand of the locality. Despite of the high investment costs, the biomass-based polygeneration system would cost 22% less over the project lifetime than the fossil-fuel based reference system while being less dependent on fuel price changes. It would also reduce CO2 -emissions by over 98%. Highlights: Presenting a control strategy for polygeneration systems using biogas and batteries Development of a model for such systems enhanced with PV and membrane distillation Application of the model in a case study for a rural locality in Bolivia Results show 22% lower lifetime costs and 98% less emissions but high capital costs The model including the control strategy facilitate designing polygeneration HESS